2015
DOI: 10.5455/ijmsph.2015.25032015289
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of epithelial ovarian tumors with HER2/neu expression by the carcinomas among patients admitted in a tertiary care hospital in Eastern India

Abstract: Background: Women in India constitute a neglected part of the society and their sufferings are least highlighted. Ovarian cancer is a fatal disease that affects them silently. Its incidence is rising with progressively enlarging elderly population. Early diagnosis is challenging, since majority of the cases of ovarian carcinomas are detected in advanced stage with nonspecific symptoms. Neo-adjuvant chemotherapy, a useful therapeutic modality, is limited by toxicity and resistance. Hence, targeted therapy is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Mucinous carcinoma did not show positive expression of Her2/neu. This finding is concordant with the study done by Sarkar et al (2015), 19 Verma et al (2018) and Goel et al (2014) 20 where 35%, 69.37% and 72.2% serous carcinoma were Her2/neu positive respectively. In the study done by Sarkar et al, only serous carcinoma showed Her2/neu positivity.…”
Section: Discussionsupporting
confidence: 92%
“…Mucinous carcinoma did not show positive expression of Her2/neu. This finding is concordant with the study done by Sarkar et al (2015), 19 Verma et al (2018) and Goel et al (2014) 20 where 35%, 69.37% and 72.2% serous carcinoma were Her2/neu positive respectively. In the study done by Sarkar et al, only serous carcinoma showed Her2/neu positivity.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are comparable with studies done by Sarkar et al 1 and Goel S et al 2 Serous tumours formed the majority with 59.3% followed by 35.2% mucinous tumours, 3.3% clear cell carcinomas, 1.1% malignant Brenner tumour and 1.1% seromucinous carcinoma. These findings were comparable with studies by Sarkar et al 1 and Sylvia et al 3 Table 1 In the present study, among the various malignant tumours, serous malignancies formed the largest group with 57.6% followed by mucinous carcinomas (27.3%), clear cell carcinomas (9.1%), malignant Brenner (3%) and seromucinous carcinoma (3%). These findings are comparable with study by Sarkar et al, which also demonstrated serous malignancy predominance with 70% followed by mucinous 20%, Brenner 5% and others 5%.…”
supporting
confidence: 91%
“…Traditionally the five main subtypes of epithelial ovarian cancer are serous, mucinous, endometrioid, clear cell and transitional cell (Brenner type) tumors. 4 HER-2 (human epidermal growth factor receptor-2) protooncogene encodes a transmembrane glycoprotein belonging to EGFR tyrosine kinase receptor family. Over-expression of HER-2 initiates intracellular signalling pathways involved in cell proliferation, differentiation, migration and apoptosis.…”
Section: Introductionmentioning
confidence: 99%